Effect of unilateral and bilateral plyometric training on jumping, sprinting, and change of direction abilities: a meta-analysis - Zhanming Zhang; Wenhao Qu; Wuwen Peng; Jian Sun; Jiyang Yue; Lingju Guan; Min Lu; Duanying Li (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Plyometric training is a commonly employed method to enhance explosive strength in athletes. However, to date, no study has provided a comprehensive and systematic evaluation of the effects of unilateral (UNI) versus bilateral (BI) plyometric training. Objectives This meta-analysis investigates the impact of UNI and BI plyometric training on jumping, sprinting, and Change of Direction (COD) abilities. Study eligibility criteria To be eligible for inclusion in the meta-analysis, the study had to be:(1)healthy individuals; (2)UNI and BI plyometric training ; (3)conducted on rigid surfaces; (4)the outcome indicators were jumping ability, sprinting, and change of direction ability; (5)randomized controlled trials (RCTs). Study appraisal and synthesis methods We used the random-effects model for meta-analyses. Effect sizes (standardized mean difference), calculated from measures of horizontally oriented performance, were represented by the standardized mean difference and presented alongside 95% confidence intervals (CI). Data sources PubMed, Web of Science, Scopus, ProQuest, CNKI and Google Scholar. Results A total of 11 papers met the inclusion criteria. The meta-analysis revealed that UNI contrast training was more effective than BI contrast training in improving single-leg jump performance (ES = 0.53, 95% CI: 0.02–1.04; Z = 2.05, p = 0.04), double-legs jump performance (ES = -0.07, 95% CI: -0.23–0.09; Z = 0.88, p = 0.38),sprint performance (ES = -0.04, 95% CI: -0.07–-0.01; Z = 2.32, p = 0.02), as well as COD (ES = − 0.08, 95% CI: − 0.12 to − 0.03; Z = 3.29, p = 0.001 < 0.01). Conversely, BI contrast training showed a greater effect on bilateral jump performance (ES = -0.07, 95% CI: -0.12–-0.03; Z = 3.39, p = 0.0007). Training with low-ground-contact frequencies (LGCF, fewer than 900 contacts) was found to significantly enhance vertical jump performance (ES = 0.64, 95% CI: 0.01–1.27; Z = 2.00, p = 0.05). Conclusions UNI and BI plyometric training offer modality-specific benefits for enhancing single-leg jumping, sprinting, and COD performance, whereas BI is more effective for optimizing bilateral jump performance. The LGCF protocol significantly enhances vertical jump performance.